Periodic locally compact groups : a study of a class of totally disconnected topological groups - Herfort, Wolfgang; Hofmann, Karl Heinrich; Russo, Francesco G. (De Gruyter studies in mathematics, 2019)
"This authoritative book on periodic locally compact groups is divided into three parts: The first part covers the necessary background material on locally compact groups including the Chabauty topology on the space of closed subgroups of a locally compact group, its Sylow theory, and the introduction, classification and use of inductively monothetic groups. The second part develops a general structure theory of locally compact near abelian groups, pointing out some of its connections with number theory and graph theory and illustrating it by a large exhibit of examples. Finally, the third part uses this theory for a complete, enlarged and novel presentation of Mukhin's pioneering work generalizing to locally compact groups Iwasawa's early investigations of the lattice of subgroups of abstract groups."--Provided by publisher.